PENGARUH PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN DI KOTA BAUBAU - Pardana, Deki; Rusmiati, Rusmiati (JITAA : Journal Of International Taxation, Accounting And Auditing, 2023)
The purpose of this study was to determine the cultural, social, personal, and psychological factors that influence purchasing decisions. Data analysis method using multiple linear regression. The results of the study that: 1) cultural variables have a positive and significant effect on purchasing decisions (3.671) and 0.001.2) The effect of social variables on purchasing decisions is negative (-0.803) and significant (0.003).3) Personal variables have a positive influence on purchasing decisions. positive and significant effect (3.458) on purchasing decisions or negative and significant effect (3.458).4) Psychological variables have a positive and significant effect on purchasing decisions, or psychology has a positive and significant effect on purchasing decisions, with a coefficient of 4.550 and a significance level of 0.002.5). Based on the results of the coefficient of determination test of 0.558, cultural, social, personal, and psychological factors have a 55.8% effect on purchasing decisions.